The Use of Non-Hormonal Contraception in Women of Fertile Age - Rohmah, Hajar Nur Fathur (Universitas Islam Lamongan, 2023)
Long-term use of hormonal contraception has various effects on acceptors. These side effects can be minimized by using non-hormonal contraceptives (condoms, IUDs, MOW) where their use is still very low. The purpose of this study was to determine the factors associated with the use of non-hormonal contraceptives in WUS. The research design is quantitative with a cross sectional approach. The sample of this study was 194 women of childbearing age who were taken by random technique. Data were collected using a questionnaire. The statistical test used was univariate with percentage, bivariate with chi square and multivariate with logistic regression. The results of the bivariate analysis of several variables showed that there was a relationship between age (p = 0.049), service availability (p = 0.000) with the use of non-hormonal contraceptives. While the variables of knowledge, husband's support, parity, family income, information on health workers and access proved to have no relationship with the use of contraceptives.